Co-gasification of rice husk and waste crumb rubber in a semi-industrial gasifier Experimental insights into enhanced performance and operational stability - Parathesi, Manikandan (Waste management (New York, N.Y.), 2025)
Copyright © 2025 Elsevier Ltd. All rights reserved.